Nexus of Asean-5 trade and economic growth - Roy Albert, Jion. (Universiti Malaysia Sarawak, UNIMAS, 2007)
This study aims to estimate the robustness of the relationship between aggregate exports, imports and Gross Domestic Product (GDP) per capita in the ASEAN - 5 economy for 30 years starting from 1974 to ye ar 2003. Proliferation of economic integration, particularly with additional new trading partner like China starting from 1997, will largely determine the scale of nexus between ASEAN - 5 trade and economic growth performances. 4 types of methods applied in this study which includes Augmented Dickey Fuller (ADF) Unit Root test, Johansen and Juselius Cointegration Test, pairwise Granger Causality as well as Vector Error Correction (VEC) Estimates. The ADF Unit Root test implies that all data are stationary in their first difference. Through the execution of Cointegration test, results reported the existent of at most one single cointegrating vector in the long run period. Based on the Granger Causality test, the results suggested in the case of short run, unidi rectional causality from GDP per capita to aggregate exports and imports existed. Besides, by harnessing Vector Error Correction Estimates in this study, significant positive nexus were found among prevailing variables, thus revealing that trade in ASEAN - 5 have positive impacts on profoundness of GDP per capita both in the short run and long run timeframe.